MUST LOVE FLOWERS - Macomber, Debbie (New York : Random House Large Print, 2023)
Joan Sample is not living the life she thought she would. But after another birthday spent alone, she is finally inclined to listen to her sister, who has been begging Joan to get back out into the world. With her encouragement, Joan makes big strides, taking care of her overgrown lawn, making new friends through a grief support group, and even renting out a room to a local college student. Across town, Maggie Herbert works mornings as a barista, before taking afternoon classes to become a nurse practitioner. But she begins to envision a new future when she finds a room for rent at a reasonable price, with a landlady who seems nice enough. Only after she moves in does she realize that her least favorite customer happens to be Joan's son--and she's just taken his childhood room. And as they confront the trials of life, new love, and family, the two women offer each other the support they had been missing. But will the risks they take be worth it in the end? --
NOT YET PUBLISHED ; DUE JULY 11, 2023.
Keywords: Large type books; Romance fiction